Stakeholders in Building Conflict Resolution Networks in Islamic Educational Institutions - Mansur, Muhamad; Fitriani, Iwan; Yusuf, Yusuf (International Journal of Educational Narratives, 2024)
Background. The objective of this research is to discuss the concept and identification of stakeholders, emphasizing the need for a holistic understanding of the various parties involved in the educational process, such as principals, teachers, parents, the government, and the community. The involvement of stakeholders in building conflict resolution networks is a primary focus, considering the complexity of global challenges and educational dynamics. Purpose. To discuss the concept and identification of stakeholders, emphasizing the need for a holistic understanding of the various parties involved in the educational process. Method. The method used in this research is a literature review through stakeholder analysis, which identifies power, legitimacy, and urgency to help determine who or what is truly considered in decision-making. Results. The first research result shows a variety of approaches and strategies for addressing conflicts, both in Islamic boarding schools (pesantren), Islamic educational institutions, and at the national level. There is an awareness of the role of Islam and religious values in conflict resolution, as well as the importance of pluralism and multicultural education. Leaders of Islamic educational institutions are considered to have a key role in conflict resolution. Conclusion. Secondly, the stakeholders involved in the context of conflict resolution research in pesantren and Islamic educational institutions include various parties who have interests and roles in conflict resolution efforts and educational development.